Social media use and its connection to gender, self-esteem and anxiety - Arnheiður Guðmundsdóttir 1989- (2017)
Facebook is a way for people to keep tabs on their friends and family while also constructing an image and identity for themselves. One of the main reasons why individuals use Facebook is to get attention and recognition from peers, friends and family. Research has shown that self-esteem decreases considerably during adolescence and that anxiety disorders have in most cases an onset in childhood or adolescence. Therefore, the aim of the study was to look at whether Social Media has an impact on self-esteem and anxiety with adolescents and whether there was any gender difference. Participants in the study were students in the 8th to 10th grade in Iceland in February 2016. The implementation and interpretation of the study was commissioned by ICSRA at Reykjavik University. The results showed that with increased use of social media both genders experienced higher levels of anxiety and lower self-esteem. Results also showed that girls experienced higher levels of anxiety and lower self-esteem than boys and the social media use seems to affect their anxiety and self-esteem more than it does for the boys. Keywords: self-esteem, anxiety, gender differences, social media, Facebook. Facebook er leið fyrir fólk til að fylgjast með vinum sínum og fjölskyldu en einnig að búa til ímynd og sjálfsmynd fyrir sig. Ein helsta ástæðan fyrir því að einstaklingar nota Facebook er að fá athygli og viðurkenningu frá jafningum, vinum og fjölskyldu. Rannsóknir hafa sýnt að sjálfsálit minnkar verulega á unglingsárum og að kvíðarröskun hefur í flestum tilfellum upphaf í æsku eða á unglingsárum. Markmið rannsóknarinnar var að skoða hvort samfélagsmiðlar hafi áhrif á sjálfsálit og kvíða hjá unglingum og hvort það hafi verið kynjamunur. Þátttakendur í rannsókninni voru nemendur í 8. til 10. bekk á Íslandi í febrúar 2016. Framkvæmd og túlkun rannsóknarinnar var framkvæmd af Rannsókn og Greiningu sem starfrækt er við Háskólann í Reykjavík. Niðurstöðurnar sýndu að með aukinni notkun samfélagsmiðla upplifðu bæði kynin meiri kvíða og minna ...